The Relationship between Blood Pressure with P-Selectin in Indonesian Hypertension Patients - R. Mustarichie (Journal of Global Pharma Technology, 2019)
Objective: The involvement of vascular inflammation is shown in the initiation and development of hypertension. P-selectin plays an important role in the inflammatory response through the initiation of leukocyte adhesion in platelets and endothelial cells. The purpose of this research was to determine the relationship between blood pressure and P-selectin in Indonesian hypertensive patients. Methods: The cross-sectional design study was conducted in 56 patients with hypertension, aged 40 to 60 years, blood pressure and serum P-selectin (sP-selectin) concentration measured. sP-selectin was determined by a colorimetric ELISA sandwich. Interpretation of the relationship between blood pressure components and sP-selectin concentration was carried out by statistical analysis. Results: It was found that sP-selectin level did not correlate significantly with systolic blood pressure (r = 0.078; P = 0.568), diastolic blood pressure (r = -0.014; P = 0.921), mean arterial pressure (r = 0.062; P = 0.648), and pulse pressure (r = 0.062; P = 0.648). Conclusion: Our results concluded that the increase in blood pressure components was not significantly associated with an increase in circulating sP-selectin concentration in hypertensive patients. Thus, there was no significant correlation between blood pressure and P-selectin in hypertensive patients. The tendency of positive results indicated an inflammatory involvement in hypertension.Keywords: Blood pressure, P-selectin, hypertension, Vascular inflammation adhesion, ELISA.